Correction: Preclinical Evidence of Anti-Tumor Activity Induced by EZH2 Inhibition in Human Models of Synovial Sarcoma. - Satoshi Kawano; Alexandra R Grassian; Masumi Tsuda; Sarah K Knutson; Natalie M Warholic; Galina Kuznetsov; Shanqin Xu; Yonghong Xiao; Roy M Pollock; Jesse J Smith; Kevin W Kuntz; Scott Ribich; et al. (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0158888.].